Sistem Monitoring dan Kendali Tegangan 3 Phase Pompa Air PDAM Berbasis ESP32 - Muhammad Zainal; Herwin Piter; A. Muhammad Syafar (Jurnal Sintaks Logika, 2025)
Currently PDAM 3-phase water pump voltage monitoring is still manual, handling problems such as damage, loss of phase voltage, is difficult to detect quickly. However, this research aims to make it easier and save time in monitoring the voltage and current on the panel, especially when the voltage on one of the phases does not match the specified parameters. This research uses an experimental method, by testing the function of a series of tools using ESP32, PZEM 004T Sensor, I2C LCD Module, SSR Module, Buzzer, and the Telegram Bot application as data receivers. The research results show that this tool can identify problems that occur on the panel. The results of the measurement data for voltage readings on measuring instruments and sensors show an error rate in the R phase = 0.34%, S phase = 0.32%, T phase = 0.52% and comparison results in the current phase R = 6.7%, S phase = 2.3% T phase=3.56%. The sensors used to read voltage and current have a low error rate and are good to use.